PENGARUH KINERJA LINGKUNGAN, BIAYA LINGKUNGAN, KEPEMILIKAN SAHAM PUBLIK, GREEN ACCOUNTING, DAN STRUKTUR MODAL TERHADAP KINERJA KEUANGAN DENGAN METODE RETURN ON EQUITY - Rodjo , Zowdtse Aliranggawa; Muharram , Salman Alfarisi (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study investigates the influence of environmental performance, environmental costs, public ownership, green accounting, and capital structure on financial performance using the return on equity (ROE) method. The primary issue addressed concerns the interplay of environmental and financial factors in shaping organizational performance. The objective is to discern the extent to which these variables collectively impact ROE. Employing a quantitative approach, data is gathered from financial reports and environmental disclosures of publicly traded companies. Novelty lies in the integration of green accounting practices with traditional financial analysis to assess environmental performance's impact on financial metrics. Findings reveal significant relationships between environmental performance, environmental costs, public ownership, green accounting, and capital structure with ROE. Environmental performance positively influences ROE, while environmental costs exhibit a negative relationship. Public ownership and green accounting practices are found to positively affect ROE, indicating the importance of stakeholder orientation and sustainability reporting in enhancing financial performance. Moreover, capital structure demonstrates a nuanced relationship with ROE, suggesting the need for further exploration. In conclusion, organizations can enhance financial performance by improving environmental performance, adopting green accounting practices, and considering stakeholder interests. Future research should delve deeper into the dynamics of capital structure and explore additional variables that may influence financial performance in the context of sustainability.